The Use of One-Part Directives in Developing Play Skills in Children With Autism During Trial-Based Instructions - Lao-Namocot, Maria Lourdes (PT. Antis International Publisher, 2024)
Play is one of the core deficits in autism. Children with autism have very different play behavior. The current study examines the of using a one-part directive during trial-based instructions on developing play skills in young children with autism. With the use of Single-subject research as an in-depth type of quantitative study of the response of an individual or a group of individuals to intervention. Participants were five children diagnosed with autism ages three to five years old. The task was introduced in a single case design across all sessions in both generalization settings. The participants seemed to have no apparent intervention effects, and one showed a decrease in play following the intervention. The possible reasons for the variability across participants and suggestions for improving methods in developing play skills are discussed. Acquisition and generalization of play skills may be affected not only by which play skills are taught but also by how play skills are taught. The careful selection of play activities may develop spontaneous play among children with autism and their peers.